INVESTIGATION OF THE 8TH GRADE STUDENTS’ ALGEBRAIC THINKING SKILLS WITH SOLO TAXONOMY - Pınar ANAPA SABAN (Fırat University, 2019)
The purpose of this study was to investigate 8th grade students’ algebraic thinking skills listed in the form of formulizing generalizations, using symbols and algebraic relations and utilizing multiple representations with SOLO Taxonomy. Following the qualitative research methods, this study was carried out during the spring semester of 2011-2012 academic year on 15 students at eighth grade whom are chosen from a school in İnegöl the town of Bursa. Participants were chosen from 8th grade students according to maximum